2023
DOI: 10.1093/jimb/kuad019
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inducers of actinobacteria natural product biosynthesis

Amir Y Alwali,
Elizabeth I Parkinson

Abstract: Actinobacteria are a large and diverse group of bacteria that are known to produce a wide range of secondary metabolites, many of which have important biological activities, including antibiotics, anti-cancer agents, and immunosuppressants. The biosynthesis of these compounds is often highly regulated with many natural products being produced at very low levels in laboratory settings. Environmental factors, such as small molecule elicitors, can induce the production of secondary metabolites. Specifically, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
0
1
0
Order By: Relevance
“…Proteobacteria, comprising numerous pathogenic and commensal species, can modulate immune responses and are integral to maintaining the microbial balance in the gut ( 36 ). Actinobacteria, characterized by their role in organic matter decomposition, contribute to nutrient cycling and may have immunomodulatory effects on the host ( 37 ). The intricate interplay between these bacterial phyla in the gastrointestinal tract underscores their significance in promoting digestion, nutrient absorption, and overall animal well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria, comprising numerous pathogenic and commensal species, can modulate immune responses and are integral to maintaining the microbial balance in the gut ( 36 ). Actinobacteria, characterized by their role in organic matter decomposition, contribute to nutrient cycling and may have immunomodulatory effects on the host ( 37 ). The intricate interplay between these bacterial phyla in the gastrointestinal tract underscores their significance in promoting digestion, nutrient absorption, and overall animal well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria is known to produce a wide range of secondary metabolites and facilitate the development of AS through modulating the ubiquitination of IκB-α which may contribute to the activation of NF-κB signaling and the accumulation of proinflammatory factors in patients with AS [ 2 , 41 ]. A case-control study have reported that fecal microbiota in AS patients was characterized by a higher abundance of Actinobacteria [ 7 ].…”
Section: Discussionmentioning
confidence: 99%